Female Leadership in The Era of AI and Fintech for Empowerment, Technology Ethics, and Digital Entrepreneurship - Djafri, Novianty; Wolok, Tineke; Lamatenggo, Nina; Solihin, Dwi Indah Yuliani; Badu, Syamsu Qamar (PPSDP International Journal of Education, 2025)
Female leadership in the era of AI, Fintech, and digital entrepreneurship has become a highly relevant and important topic in the context of economic and social development. This study aims to analyze the role of female leadership in leveraging AI, Fintech, and digital entrepreneurship technologies to empower women and promote gender equality. The method employed is a literature review on several female leaders in the technology and finance sectors. The results showed that female leadership plays a crucial role in utilizing AI, Fintech, and digital entrepreneurship to enhance financial accessibility, increase income, and promote gender equality. This study also discusses technology ethics and digital entrepreneurship, as well as the challenges and opportunities faced by female leaders in the digital era. This research contributes to serve as a reference for leaders, policymakers, and academics in strengthening the role of female leadership in the digital era.